Applications of seismic hazard assessment methods in mines - G. van Aswegen (The Southern African Institute of Mining and Metallurgy, 2003)
Large structures in mines (faults, dykes, pillars, abutments) fail when the load exceeds the strength. If the loading system stiffness (LSS, also referred to as the ‘local mine stiffness’) is lower than the stiffness of the structure the failure will be unstable. The greater the difference between these stiffnesses, the greater the energy release during unstable failure. A method has been formulated by which the LSS is established through cost-effective numerical modelling while insight into the structure stiffness (source stiffness - SS) is provided by apparent stiffness, a parameter based on the empirical relation between seismic moment and radiated seismic energy of small seismic events from the area/volume of interest. By plotting LSS vs SS a ‘stiffness diagram’ is constructed that is useful for seismic hazard ranking of different structures. A comparative back-analysis of the Dagbreek fault in Welkom, South Africa, (source of the 1990 Matjhabeng earthquake) and two other nearby faults confirm the applicability of the method. An extension of the method, where ‘hazard magnitude’ is used as a measure of the LSS, allows a ‘stiffness diagram’ to be constructed using seismic data only. Les larges structures dans les exploitations minières (failles, dikes, piliers, culées) s’écroulent lorsque la charge dépasse la résistance. Si la raideur du système de chargement (LSS, aussi appelé la « raideur de la mine locale ») est plus basse que la raideur de la structure, l’éboulement sera instable. Plus la différence est grande entre ces deux raideurs, plus l’énergie dégagée pendant l’éboulement instable est grande. Une méthode a été formulée selon laquelle le LSS est établi par modélisation numérique rentable, tandis que la raideur de la structure (SS – raideur de la source) est établie par la raideur apparente, un paramètre basé sur la relation empirique entre le moment sismique et l’énergie sismique radiée de petits moments sismiques dans l’aire/volume en question. On trace le « diagramme de raideur » en relevant les deux mesures (LSS et SS), ce qui est utile pour classer les risques sismiques de structures différentes. On vérifie l’applicabilité de la méthode en comparant la faille de Welkom, Afrique du Sud (foyer du séisme de Matjhabeng en 1990) avec deux autres failles proches. Une extension de cette méthode, dans laquelle on utilise la « magnitude du risque » comme mesure du LSS, permet de construire le « diagramme de raideur » avec des données sismiques seulement. Große Strukturen in den Gruben (Verwerfungen, Dämme, Pfeiler, Auflager) scheitern, wenn die Last die Stärke übersteigt. Wenn die Steifheit des Ladesystems (LSS, auch bezeichnet als `lokale Grubensteifheit’) niedriger ist als die Steifheit der Struktur wird der Bruch instabil. Je grösser der Unterschied zwischen diesen Steifheiten, desto grösser die Energiefreigabe während des instabilen Bruches. Es wurde eine Methode formuliert, durch die das LSS durch eine kosteneffektive numerisches Modell erstellt wird, während ein Einblick von der offensichtlichen Steifheit in die Struktursteifheit (Quellensteifheit - SS) gegeben ist, ein Parameter der auf der emipirischen Relation zwischen seismischem Moment und ausgestrahlter seismischer Energie von kleinen seismischen Ereignissen vom Interessens-/Volumenbereich basiert. Durch das Kartograpahieren der LSS in Bezug auf die SS wird ein `Steifheitsdiagramm ' konstruiert, welches für seismische Gefahrklassifizierung der unterschiedlichen Strukturen nützlich ist. Eine vergleichende Postanalyse der Dagbreek Verwerfung in Welkom, Südafrika, (Zentrum des Matjhabeng Erdbebens 1990) und in zwei anderen nahe gelegenen Verwerfungen bestätigen die Anwendbarkeit der Methode. Eine Verlängerung der Methode, in der die `Gefahrengröße' als Maß für das LSS verwendet wird, gestattet, daß ein `Steifheitsdiagramm' konstruiert wird, welches nur seismische Daten verwendet.